THE ACTIVITY OF USMON KHODJA PULATKHODJAEV IN REFORMING THE EDUCATION SYSTEM IN THE EMIRATE OF BUKHARA AND THE ESTABLISHMENT OF NEW METHODICAL SCHOOLS (Scientific journal of the Fergana State University, 2023)
This article reveals the activities of the progressive person and patriot Usmon Khoja Pulatkhodjaev in the modernization of education in the Emirate of Bukhara and the establishment of new methodological schools through the analysis of sources.